2016
DOI: 10.1016/j.landusepol.2015.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of urban developments on the functional connectivity of forested habitats: a joint contribution of advanced urban models and landscape graphs

Abstract: International audienceThe impacts of urban growth on biodiversity vary according to the form and the intensity of urbanisation.However, there is a lack of knowledge about the consequences of the type of urban structure (e.g. mono-centric vs polycentric), the shape of urban boundaries, the local density of residential development, on the habitats of wildlife species. In this context, this paper focuses on the relationship between forms ofurbanisation and functional connectivity of ecological habitats. In the ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 63 publications
0
36
0
6
Order By: Relevance
“…Our workflow can, however, be applied to any level of complexity in scenario or model design. For example, the IFM could be adapted to incorporate the increased complexity in functional connectivity found in urban landscapes (Tannier et al 2016) instead of Euclidean distance between patches (e.g. Watts and Handley 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Our workflow can, however, be applied to any level of complexity in scenario or model design. For example, the IFM could be adapted to incorporate the increased complexity in functional connectivity found in urban landscapes (Tannier et al 2016) instead of Euclidean distance between patches (e.g. Watts and Handley 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, this kind of fragmentation (sprawl) can be partially mitigated by the possibility of species movement in the interstitial zones of the urban development. The barrier effect depends on the shape and intensity of urbanisation (Alberti, 2005) and is generally intensified in the case of compact and dense cities (Tannier et al, 2016). In terms of transport infrastructure, fragmentation occurs by disconnection and reinforces the barrier effect, often over several tens of kilometres (Forman, Alexander, 1998;Fu et al, 2010;Girardet et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have focused on a retrospective approach by assessing connectivity losses caused by the construction of major transport infrastructures (e.g., Fu et al, 2010;Clauzel et al, 2013;Girardet et al, 2013). Other studies have used a prospective approach by assessing the potential impact of different land-use planning scenarios, such as the construction of a new highway (Vasas et al, 2009) or new residential development areas (Tannier et al, 2012(Tannier et al, , 2016. These studies have focused on the overall impact of a development or major transport infrastructure on a regional scale (calculation of a global connectivity metric) or habitat patches (calculation of a local metric).…”
Section: Introductionmentioning
confidence: 99%
“…Studies combining SDM and spatial graphs showed the relevance of both modelling approaches (Duflot et al, 2018;Rödder et al, 2016), but further research is required to better incorporate them into environmental assessment of development projects and to guide decision-making. In addition, these approaches have been mostly applied to large urban project (Tannier et al, 2016) or to major transportation infrastructure projects (Clauzel et al, 2013;Mimet et al, 2016), but not to smaller development projects also subject to EIA (like residential neighborhoods, industrial and commercial areas, sports and leisure facilities, housing developments, etc.). However, these smaller projects and their multiplication severely impact the habitats of some suburban species, hence decreasing their moves and populations (Ayram et al, 2017).…”
Section: Introductionmentioning
confidence: 99%